Integrating binding affinity and tonic signaling enables a rational CAR design for augmented T cell function - Arpad Szoor; Gyorgy Vereb; Hinrich Abken; Markus Barden; Patrick Ronan Elsenbroich; Vivian Haas; Moritz Ertelt; Philip Pervan; Lukas Velas; Bence Gergely; Dennis Christoph Harrer; Valerie Bezler; et al. (Journal for ImmunoTherapy of Cancer)
Background The success of chimeric antigen receptor (CAR) T cell therapy for hematological malignancies has not yet translated into long-term elimination of solid tumors indicating the need for adequately tuning CAR T cell functionality.Methods We leveraged a translational pipeline including biophysical characterization and structural prediction of the CAR binding moiety, evaluation of cellular avidity, synapse formation, T cell motility, and functional capacities under repetitive target challenge and in sustained tumor control.Results As an example of clinical relevance, we derived a panel of anti-Her2 CARs covering a 4-log affinity range, all expected to target the same Her2 epitope. The same scFv mutations increased both antigen-specific affinity, cellular avidity, and antigen-independent “tonic” signaling; above a minimum threshold, raise in affinity translated into functional avidity in a non-linear fashion. In this case, replacement by amino acids of higher hydrophobicity within the scFv coincidentally augmented affinity, non-specific binding, spontaneous CAR clustering, and tonic signaling, all together relating to T cell functionality in an integrated fashion.Conclusions Data emphasize that tonic signaling is not always due to the positive charge but can be driven by hydrophobic interactions of the scFv. CAR binding affinity above the threshold and tonic signaling are required for sustained T cell functionality in antigen rechallenge and long-term tumor control.